Features of combat trauma pathogenesis - V.V. Makarov; V.V. Nehoduiko; V.M. Feskov; O.H. Petiunin; K.M. Smolianyk; M.Yu. Syzyi (Медицина неотложных состояний)
The world trend of military surgery of last decades is an improvement of treatment outcomes in combat trauma, the reduction of both early and late mortality, which is associated with the training of combatants in providing first aid, self-help, improving medical logistics, implementing the principles of damage control surgery and early resuscitation, staging of assistance. However, in the structure of mortality, especially late, the leading positions, as before, belong to acute lung damage, acute respiratory distress syndrome, multiple organ failure whose pathogenesis is considered in this review. The conceptual tool of this study goes beyond the usual surgical one. However, just as combat trauma requires a multisystem approach, so the solution to the problem of multiple organ failure can be found only with the interaction of various disciplines, and therefore only this level of understanding of this problem opens the prospect of further development.